2020
DOI: 10.5336/dermato.2020-74503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatment with Methotrexate and TNF Alpha Inhibitors on Insulin Resistance in Patients with Psoriasis

Abstract: Psoriasis, a chronic inflammatory skin disease, is also known to be associated with various comorbidities. 1 Recently, the increased prevalence of obesity, hyperglycaemia, dyslipidaemia and arterial hyper-tension, all of which are also components of metabolic syndrome, have also been reported in psoriasis patients. Psoriasis is also considered to be associated with increased risk of cardiovascular diseases. 2-5 The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The literature search identified 558 publications, of which 59 were fully reviewed and 20 studies (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) were finally eligible for inclusion. Figure 1 and Supplementary Appendix 2 illustrate the detailed information of the literature selection procedure.…”
Section: Search Resultsmentioning
confidence: 99%
“…The literature search identified 558 publications, of which 59 were fully reviewed and 20 studies (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) were finally eligible for inclusion. Figure 1 and Supplementary Appendix 2 illustrate the detailed information of the literature selection procedure.…”
Section: Search Resultsmentioning
confidence: 99%
“…Similarly, Farshchian et al reported that baseline CRP levels among psoriatic patients were higher than normal [ 21 ]. Moreover, Strober et al and Demir et al concluded that clinical response in psoriasis patients was associated with greater CRP reductions [ 22 , 23 ]. Concerning TNFα levels in response to psoriasis therapy, several studies found that serum levels of TNFα in patients with psoriasis were significantly higher than in the control group.…”
Section: Discussionmentioning
confidence: 99%